x+(-35)=18
x = 18 - ( - 35 )
x = 53
2x - ( - 17 ) = 15
2x + 17 = 15
2x = 15 - 17
2x = -2
x = -2 : 2
x = -1
Đúng 0
Bình luận (0)
x+(-35)=18
x = 18 - (-35)
x = 53
vậy___
2x- (-17) = 15
2x = 15 + (-17)
2x = 32
x = 32 : 2
x = 16
vậy____
Đúng 0
Bình luận (0)
\(x+\left(-35\right)=18\)
\(x=18+35\)
\(x=53\)
\(2x-\left(-17\right)=15\)
\(2x=15-17\)
\(2x=-2\)
\(x=-1\)
Đúng 0
Bình luận (0)
x+(-35)=18
=> x = 53
2x- (-17) = 15
=> x = -1
Chúc bn học giỏi!
Đúng 0
Bình luận (0)
x+(-35)=18
x - 35 = 18
x = 53
2x- (-17) = 15
x= -1
Đúng 0
Bình luận (0)
1/x+(-35)=18
x=18-(-35)
x=53
2/ 2x-(-17)=15
2x=15+(-17)
x=(-2):2
x=-1
Đúng 0
Bình luận (0)
x + (-35) = 18
=> x = 18 - (-35)
=> x = 18 + 35
=> x = 53
Vậy x = 53
2x - (-17) = 15
=> 2x + 17 = 15
=> 2x = 15 - 17
=> 2x = -2
=> x = -2 : 2
=> x = -1
Vậy x = -1
Đúng 0
Bình luận (0)
x+(-35)=18
x=18-(-35)
x=53
2x-(-17)=15
2x=15+(-17)
2x=-2
x=-1
Đúng 0
Bình luận (0)